1996
DOI: 10.3109/10641969609081036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hemodynamics, Vascular Reactivity and Baroreceptor Compensation in the Insulin Resistant Zucker Obese Rats

Abstract: Incidence of essential hypertension has been reported to be significantly higher in the population afflicted with non-insulin dependent diabetes mellitus (NIDDM). The present studies were under taken in the insulin resistant, Zucker obese rats to evaluate various factors that could lead to the development of high blood pressure. Direct blood pressure measurements in the conscious obese rats indicated that they were not consistently hypertensive although the blood pressures of the obese rats tended to be higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
29
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
13
29
0
1
Order By: Relevance
“…Plasma glucose level and blood pressure in Zucker-fatty rats are relatively similar to those in Zucker-lean rats [14,20]. These characteristics show that the Zucker-fatty rat may be suitable for research on effects of insulin resistance on autonomic nervous function.…”
Section: Introductionmentioning
confidence: 52%
“…Plasma glucose level and blood pressure in Zucker-fatty rats are relatively similar to those in Zucker-lean rats [14,20]. These characteristics show that the Zucker-fatty rat may be suitable for research on effects of insulin resistance on autonomic nervous function.…”
Section: Introductionmentioning
confidence: 52%
“…Zucker rats have been described as being both hypertensive and normotensive. Several studies indicate that ZFR are hypertensive compared with phenotypically normal heterozygous insulin-sensitive ZLR (1,10,24,50), whereas other studies show a normotensive state of ZFR (30,35,36). Several studies (10,19,45,47) indicate higher levels of SNA in homozygous Zucker rats than in phenotypically normal heterozygous Zucker rats (fa/Ϫ), and it has been suggested that alterations in sympathetic function in obese Zucker rats can be tissue specific (30).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Zucker rats are insulin resistant, hyperinsulinemic, and obese. Previous studies on the link between alterations of blood pressure and SNA in the presence of insulin resistance in this strain have yielded contradictory results (1,10,19,24,30,35,36,47,50) that might to be caused, in part, by limitations of the assessment of the degree of alterations of glucose kinetics.We showed previously in the spontaneously hypertensive rat (SHR) and its related control strain (33, 34) that a suitable characterization of the dynamics of glucose kinetics is obtained from the intravenous glucose tolerance test (IVGTT) interpreted with the minimal model (4, 16). On the other hand, an important index of SNA is provided by somatosympathetic reflexes, which are coordinated autonomic responses to activation of somatic afferents mediated by changes in sympathetic activity that cause a cardiovascular reaction to changes in the physical state of the body (14,40).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…[17][18] Enhanced central sympathetic discharge, abnormal hemodynamics and attenuated BRS were found in obese Zucker rats. [19][20] Even normotensive, obese Zucker rats have impaired chronotropic baroreflexes. 20 The blunted baroreflex may contribute to initial blood pressure elevation and further cause hypertension in obesity.…”
Section: Introductionmentioning
confidence: 99%